A functional cathode sodium compensation agent for stable sodium-ion batteries - Wei Wu; Zhenglin Hu; Zhengfei Zhao; Aoxuan Wang; Jiayan Luo (Green Energy & Environment)
Hard carbon (HC) is widely used in sodium-ion batteries (SIBs), but its performance has always been limited by low initial Coulombic efficiency (ICE) and cycling stability. Cathode compensation agent is a favorable strategy to make up for the loss of active sodium ions consumed by HC anode. Yet it lacks agent that effectively decomposes to increase the active sodium ions as well as regulate carbon defects for decreasing the irreversible sodium ions consumption. Here, we propose 1,2-dihydroxybenzene Na salt (NaDB) as a cathode compensation agent with high specific capacity (347.9 mAh g−1), lower desodiation potential (2.4–2.8 V) and high utilization (99%). Meanwhile, its byproduct could functionalize HC with more CO groups and promote its reversible capacity. Consequently, the presodiation hard carbon (pHC) anode exhibits highly reversible capacity of 204.7 mAh g−1 with 98% retention at 5 C rate over 1000 cycles. Moreover, with 5 wt% NaDB initially coated on the Na3V2(PO4)3 (NVP) cathode, the capacity retention of NVP + NaDB|HC cell could increase from 22% to 89% after 1000 cycles at 1 C rate. This work provides a new avenue to improve reversible capacity and cycling performance of SIBs through designing functional cathode compensation agent.